REVIEW ON BIOACTIVE CERAMIC COATING - S BAG,; B K BISWAS, (International Journal of Pharma and Bio Sciences, 2016)
Currently metallic biomaterials like 316L stainless steel, Co-Cr alloys, Ti and its alloys are being used extensively as implantable biomaterials for their good mechanical properties. The necessity for innovation and development of smart materials/coatings with improved functional and bio-compatible properties, either by employing surface engineering or through improving process parameters has been felt. Bioactive HA and Bio-glass coatings over orthopedic & dental implants are used in several applications with the aim of increasing corrosion resistance of the metal and to enhance the biocompatibility & bio-stability. Some of the more commonly used techniques to deposit bioactive coating over implants include plasma deposition, physical vapour deposition, chemical vapor deposition, ion-beam sputter deposition, thermal spraying, sol-gel deposition and dipping. This review is aiming to give a comprehensive summary of bioactive coating, different coating techniques and the advantages and disadvantages of bioactive coating.